The Response of Mortgage Supply to Expected Flood Insurance Lapses - Hu, Zhongchen (Review of Financial Studies, 2026)
Abstract Flooding is among the costliest natural disasters in many countries. To protect collateral, many mortgage borrowers in the United States are legally required to maintain flood insurance. However, lax enforcement leads to frequent policy lapses. This paper shows that lenders provide credit contingent on borrowers’ insurance incentives. Exploiting exogenous premium rises ($266 annually) that disincentivize insurance take-up, I find mortgage denial rates dramatically increase by 0.49–0.81 pp. By comparison, lowering income by $266 has an effect of only 0.01 pp. Mortgage applicants’ composition remains unchanged, refuting demand-side explanations. Evidence suggests lenders internalize ex-post monitoring costs into ex-ante credit restrictions.